Nitrogen Use Efficiency as Affected by Phosphorus and Potassium in Long-Term Rice and Wheat Experiments - Ying-hua DUAN; Xiao-jun SHI; Shuang-lai LI; Xi-fa SUN; Xin-hua HE (Journal of Integrative Agriculture, 2014)
Improving nitrogen use efficiency (NUE) and decreasing N loss are critical to sustainable agriculture. The objective of this research was to investigate the effect of various fertilization regimes on yield, NUE, N agronomic efficiency (NAE) and N loss in long-term (16- or 24-yr) experiments carried out at three rice-wheat rotation sites (Chongqing, Suining and Wuchang) in subtropical China. Three treatments were examined: sole chemical N, N+phosphorus (NP), and NP+potassium (NPK) fertilizations. Grain yields at three sites were significantly increased by 9.3–81.6% (rice) and 54.5–93.8% (wheat) under NP compared with N alone, 1.7–9.8% (rice) and 0–17.6% (wheat) with NPK compared with NP. Compared to NP, NUE significantly increased for wheat at Chongqing (9.3%) and Wuchang (11.8%), but not at Suining, China. No changes in NUE were observed in rice between NP and NPK at all three sites. The rice-wheat rotation's NAE was 3.3 kg kg−1 higher under NPK than under NP at Chongqing, while NAE was similar for NP and NPK at Suining and Wuchang. We estimated that an uptake increase of 1.0 kg N ha−1 would increase 40 kg rice and 30 kg wheat ha−1. Nitrogen loss/input ratios were ∼60, ∼40 or ∼30% under N, NP or NPK at three sites, indicating significant decrease of N loss by P or PK additions. We attribute part of the increase in NUE soil N accumulation which significantly increased by 25–55 kg ha−1 yr−1 under NPK at three sites, whereas by 35 kg ha−1 yr−1 under NP at Chongqing only. This paper illustrates that apply P and K to wheat, and reduce K application to rice is an effective nutrient management strategy for both the NUE improvement and N losses reduction in China.